Demographic projections of depopulated zones in Serbia: The example of the municipality of Negotin - Vasić Petar; Gligorijević Vera (Glasnik Srpskog Geografskog Društva, 2023)
Demographic projections represent a multi-purpose instrument in predicting the population development for the purpose of spatial planning and organizing as well as local economic development. In Serbia, demographic projections are very rarely produced on territorial levels lower than regional, therefore, the projections that are depicted in this work will be focused on the municipality of Negotin with the goal of observing an exceptionally depopulated area located in Eastern Serbia. The projections have been created with a time horizon of the year 2040 by using the cohort-component method which is well-established in literature as a prevailing method of producing population projections. Population projections for the municipality of Negotin have been constructed in three variants all relying on the initial hypotheses of fertility, mortality, and migrations. This is also the first time that such projections have been made separately for a rural and urban area of the municipality of Negotin. Results have shown that by the year 2040, the population will range between 17 and 18 thousand citizens, with the depopulation rate in rural areas being twice as high as that of urban ones. With the current demographic state in mind, it is evident that only direct interventions in the domain of migrational policies could slow down the pace of depopulation. This is due to the fact that the current fertility potential is undoubtedly insufficient to slow down depopulation even in the occurrence of a complete response to pronatalist policies.